2014
DOI: 10.1186/bf03353401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nearby large earthquakes on the occurrence time of the Tokai earthquake—An estimation based on a 3-D simulation of plate subduction—

Abstract: An eastern half of the focal region of the 1854 Ansei-Tokai earthquake was not ruptured at the 1944 Tonankai earthquake and the area around Suruga Bay remained as a seismic gap (Ishibashi, 1981). As to the cause that the fault motion in 1944 did not extend to the eastern part, Mogi (1981) and Pollitz and Sacks (1995) considered effects of the 1891 Nobi earthquake of M8.0. In this paper, we evaluate quantitatively effects of nearby large earthquakes, the 1891 Nobi, the 1923 Kanto and the 1944 Tonankai earthquak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…In the meantime, Kuroki et al [2002, 2004] simulated the cycle of subduction zone earthquakes using a three‐dimensional fault model. When parameters were set in such a way that aseismic slip prevailed outside an isolated zone of seismic sliding, a ring‐shaped zone of high shear stress emerged around the rim of the seismically sliding region, and kept contracting with the passage of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, Kuroki et al [2002, 2004] simulated the cycle of subduction zone earthquakes using a three‐dimensional fault model. When parameters were set in such a way that aseismic slip prevailed outside an isolated zone of seismic sliding, a ring‐shaped zone of high shear stress emerged around the rim of the seismically sliding region, and kept contracting with the passage of time.…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of these pioneering studies, Kuroki et al [2004] conducted three‐dimensional modeling to evaluate the influence of great nearby earthquakes on the occurrence time of the Tokai earthquake off Japan. Liu and Rice [2007] investigated aseismic deformation events that are excited along a subducting plate boundary by a stress step.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that tensional earthquakes advance the occurrence of the next earthquake and compressional earthquakes delay it, except for later parts of the cycle, where clock advance occurs. The research was followed by Kato [] and Kuroki et al [], who examined the effects of nearby earthquakes on earthquake cycles of large interplate earthquakes at subduction zones. Kuroki et al [] used a realistic 3‐D fault geometry and evaluated the effects of three large earthquakes on the Tokai earthquake, which is expected to occur in central Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The research was followed by Kato [] and Kuroki et al [], who examined the effects of nearby earthquakes on earthquake cycles of large interplate earthquakes at subduction zones. Kuroki et al [] used a realistic 3‐D fault geometry and evaluated the effects of three large earthquakes on the Tokai earthquake, which is expected to occur in central Japan. Perfettini et al [] systematically analyzed CA on a 2‐D rate‐and‐state fault by means of loading the whole fault at various onset times within the earthquake cycle.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of their results, they calculated the afterslip during days 16-30 and compared it with the observed afterslip. Kato (2004a) and Kuroki et al (2004) examined the effects of nearby earthquakes on the occurrence time of large interplate earthquakes based on numerical simulations.…”
Section: Introductionmentioning
confidence: 99%